Aerosol‐Jet‐Printed Donor‐Blocking Layer for Organic Photodiodes. (30th November 2020) - Seiberlich, Mervin; Strobel, Noah; Ruiz‐Preciado, Luis Arturo; Ruscello, Marta; Lemmer, Uli; Hernandez‐Sosa, Gerardo
Abstract: Organic photodiodes (OPDs) are optical sensors combining high performance, lightweight mechanical flexibility, and processability from solution. Their fabrication by industrial printing techniques opens a wide range of innovative applications for emerging fields in sensing and the Internet of Things. They typically consist of printed multilayers with functionalities to absorb light, to extract charges, or to reduce detection noise. However, the printing of such device architecture poses a challenge as the deposition of a material can lead to disruption of film morphology or intermixing of materials if its solvent interacts with the previously deposited layer. This work proposes a process to print multilayers from the same solvent system utilizing the aerosol‐jet technique. By fine adjustment of the aerosol properties through the tube temperature ( T Tube ), the drying time of poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) printed layers is significantly reduced. This allows its deposition onto a P3HT‐based bulk‐heterojunction (BHJ) without negatively affecting its performance. The additional printed P3HT layer, spatially extends the donor region of the BHJ, providing ideal hole extraction and simultaneous noise reduction by the blocking of injected electrons. This donor blocking layer (DBL) yields a noise reduction of two orders of magnitude in OPDs operated under −2 V reverse bias. Abstract : Electron blocking layers for organic photodiodes are printed on top of the active layer utilizing the same solvent and material systems. The solvent content is controlled by the ink temperature in an aerosol‐jet process. This enables high‐performance devices without detrimental consequences to the bulk‐heterojunction performance.